Characteristics of Tetanic Force Produced by the Sternomastoid Muscle of the Rat. (25th May 2010) - Sobotka, Stanislaw; Mu, Liancai
Abstract : The sternomastoid (SM) muscle plays an important role in supporting breathing. It also has unique anatomical advantages that allow its wide use in head and neck tissue reconstruction and muscle reinnervation. However, little is known about its contractile properties. The experiments were run on rats and designed to determine in vivo the relationship between muscle force (active muscle contraction to electrical stimulation) with passive tension (passive force changing muscle length) and two parameters (intensity and frequency) of electrical stimulation. The threshold current for initiating noticeable muscle contraction was 0.03 mA. Maximal muscle force (0.94 N) was produced by using moderate muscle length/tension (28 mm/0.08 N), 0.2 mA stimulation current, and 150 Hz stimulation frequency. These data are important not only to better understand the contractile properties of the rat SM muscle, but also to provide normative values which are critical to reliably assess the extent of functional recovery following muscle reinnervation.